KEBIJAKAN HARI SANTRI NASIONAL DAN INOVASI KEBIJAKAN PENDIDIKAN ISLAM - Kholilur Rahman (LPPM IAI IBRAHIMY GENTENG BANYUWANGI, 2019)
This paper reviewed literature about the background of the policy on Hari Santri Nasional (HSN). Historical and political approach emphasis on historical data as well as political factors that affect its, were sought to acquire a comprehensive understanding. This study described the presidential decree about the HSN was based on the implementation of the normative values of justice in Islam political. The policy response of HSN as an integral part of public policy innovation is the moment of awakening